Water-resistant and freeze-resistant phosphogypsum gel-stabilized asphalt concrete and preparation method thereof
By introducing PU and cement into phosphogypsum asphalt concrete to form an organic-inorganic cementitious system, the water sensitivity problem of phosphogypsum asphalt pavement was solved, realizing the recycling of industrial solid waste and improving water and freeze resistance, while reducing material costs.
Patent Information
- Application Number
- CN202311128808.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-12-19
- Estimated Expiration
- 2043-09-04
AI Technical Summary
In existing technologies, when phosphogypsum is used as a filler for asphalt pavements, it has the problem of high water sensitivity, resulting in poor water and freeze resistance, and its recycling rate is low, causing environmental pollution.
An organic-inorganic cementitious system is formed by using PU and cement. Waste phosphogypsum is washed and calcined, then used as a filler and combined with modified asphalt and natural aggregates to form an organic-inorganic cementitious structure, which enhances adhesion.
It effectively consumes industrial solid waste phosphogypsum, reduces the consumption of natural mineral powder, improves the water stability and frost resistance of asphalt concrete, reduces material costs, and extends the service life of road surfaces.
Smart Images

Figure CN117049857B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of road engineering material resource utilization and recycling, in particular to an anti-water freezing type cement stabilized phosphogypsum asphalt concrete and a preparation method thereof. BACKGROUND
[0002] As the main paving form of highways in China, the proportion of asphalt pavement on various grades of roads is increasing. The paving of asphalt pavement requires a large amount of consumption of non-renewable natural stone, which makes the already scarce mineral resources even more scarce. Therefore, seeking a renewable resource to replace natural stone has important practical significance for the sustainable development of asphalt pavement.
[0003] Phosphogypsum, as a common solid waste in industrial production, has a relatively low recycling rate and is mainly treated in a simple way such as stacking and landfill, causing extremely unfriendly ecological environmental pollution. Due to the complex composition, low strength and strong water sensitivity of phosphogypsum, when phosphogypsum is used as a filler in asphalt mixture, it will reduce the adhesion between asphalt and aggregate, increase the water sensitivity of asphalt mixture, and cause serious water and frost resistance problems. Polyurethane (PU) is a new type of high molecular organic material with high temperature resistance, aging resistance and wear resistance, which has been widely used in asphalt pavement. PU prepolymer appears as a yellow-brown oily liquid, and its molecular chain contains isocyanate (-NCO). This group has a large polarity and can react with the -OH group in phosphogypsum to form a flexible curing effect. Cement, as an inorganic cementitious material, can prevent water from penetrating into the bonding interface between asphalt and aggregate by undergoing hydration reaction with the moisture in the environment and the free water in phosphogypsum, so the incorporation of cement can improve the water stability of asphalt mixture. To solve the problem of recycling, PU and cement are formed into an organic-inorganic cementitious system to serve as a functional additive for asphalt, which can enhance the adhesion between asphalt and natural aggregate and phosphogypsum, reduce the water sensitivity of phosphogypsum asphalt mixture, and prolong the service life of asphalt pavement. Therefore, it is of great practical engineering significance to solve the water and frost resistance problem of phosphogypsum asphalt concrete. SUMMARY
[0004] In view of the deficiencies in the prior art, the present application aims to provide an anti-water freezing type cement stabilized phosphogypsum asphalt concrete and a preparation method thereof to solve the problems raised in the background art. The present application can greatly consume industrial solid waste phosphogypsum, reduce the consumption of natural mineral powder, solve the specific engineering problem of phosphogypsum asphalt concrete being afraid of water and frost, and improve the water stability and frost resistance of phosphogypsum asphalt concrete.
[0005] In order to achieve the above object, the present application is realized by the following technical scheme: a water and freeze resistant cementitious stabilized phosphogypsum asphalt concrete, the raw materials of the asphalt concrete comprising PU / cement composite modified asphalt, natural aggregate and phosphogypsum, the phosphogypsum filler being fine powder obtained after water washing, calcining and grinding of waste phosphogypsum.
[0006] A preparation method of a water and freeze resistant cementitious stabilized phosphogypsum asphalt concrete, characterized in that the preparation method is used for preparing the asphalt concrete material as described above, and mainly comprises the following steps:
[0007] Step one: obtaining phosphogypsum powder after water washing, drying and grinding of recycled waste phosphogypsum;
[0008] Step two: preparing PU / cement modified asphalt by adding 4% PU prepolymer and 5% cement powder relative to the mass of asphalt, and stirring at low speed for 30 min after heating the asphalt to a molten state at 150-160℃;
[0009] Step three: quantitatively taking PU / cement composite modified asphalt, natural aggregate and phosphogypsum powder obtained in step one according to the aggregate gradation and 5.2% oil stone ratio of the water and freeze resistant phosphogypsum asphalt concrete;
[0010] Step four: preparing water and freeze resistant phosphogypsum asphalt concrete of organic / inorganic material composite stabilized phosphogypsum by mixing PU / cement composite modified asphalt, aggregate and phosphogypsum filler according to the designed mixing ratio.
[0011] Further, the particle size of the phosphogypsum filler is 0-0.075 mm; and the asphalt is 70# base asphalt.
[0012] Further, the PU / cement composite modified asphalt is prepared by melting and blending PU, cement and asphalt.
[0013] Further, the natural aggregate is continuous gradation aggregate formed by crushing limestone, and the particle size is 0.075-16 mm.
[0014] Further, the phosphogypsum filler is phosphogypsum powder obtained by screening after water washing, calcining and grinding of waste phosphogypsum.
[0015] Further, the mixing condition in step four is that the PU / cement composite modified asphalt is in a heated molten flow state, and the aggregate is dried at 150-160℃ and 160-170℃ for at least 4 h.
[0016] The present application has the following beneficial effects:
[0017] 1.The anti-frozen gel-stabilized phosphogypsum asphalt concrete and its preparation method replace all natural mineral powder in the grading with phosphogypsum powder, which can greatly consume industrial solid waste phosphogypsum and greatly reduce the consumption of natural mineral powder, thus promoting the reuse of industrial solid waste and achieving environmental protection.
[0018] 2.The anti-frozen gel-stabilized phosphogypsum asphalt concrete and its preparation method use PU and cement that can react with water to form an organic-inorganic gel structure system, which can form a rigid organic film on the surface of the aggregate and phosphogypsum to avoid water erosion, reduce the leaching of water-soluble pollutants in the phosphogypsum, and enhance the adhesion between the asphalt and the aggregate and phosphogypsum, thus improving the water resistance and frost resistance of the phosphogypsum asphalt concrete in water and ice environments and solving the specific engineering problems of water and frost resistance of the phosphogypsum asphalt concrete.
[0019] 3.The anti-frozen gel-stabilized phosphogypsum asphalt concrete and its preparation method replace the mineral powder after pretreatment by technical means, which can reduce the material cost by more than 25% and directly achieve significant economic benefits. In addition, in the process of continuous water damage, PU and cement continuously react with water to form an organic-inorganic gel structure system, which continuously improves the water stability and frost resistance of the phosphogypsum asphalt concrete and indirectly achieves significant economic benefits. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 The figure is a mineral aggregate grading curve. DETAILED DESCRIPTION
[0021] To make the technical means, creative features, purposes and effects of the present application easy to understand, the present application is further described below in conjunction with specific embodiments.
[0022] Please refer to Figure 1 , the present application provides a technical solution: an anti-frozen gel-stabilized phosphogypsum asphalt concrete and its preparation method.
[0023] In the examples and comparative examples, the following raw materials are used: 70# base asphalt with a softening point of 47.2℃, a 25℃ penetration of 67dmm, a 15℃ ductility greater than 100cm, and a 135℃ Brookfield rotational viscosity of 0.47Pa·s; natural coarse aggregate is continuously graded natural limestone coarse aggregate with a particle size of 4.75-13.2mm, an apparent density of 2.851g·cm -3 , a solidity of 8.7%, and a crushing value of 20.7%; and natural fine aggregate is continuously graded natural limestone fine aggregate with a particle size of 0.075-4.75mm, an apparent density of 2.865g·cm -3, and the sand equivalent is 77.3%; the mineral powder is obtained by washing, drying and grinding the waste phosphogypsum, and has a particle size of 0-0.075 mm and an apparent density of 2.371 g·cm -3 , and no particle agglomeration; the PU is an isocyanate compound, and the main components are diphenyl methane diisocyanate, toluene diisocyanate, polyester polyol and polyether polyol; and the cement is P·O 42.5 ordinary portland cement, and has a density of 3.15 g·cm -3 , and no particle agglomeration.
[0024] Example 1
[0025] The water-resistant / freeze-resistant phosphogypsum asphalt concrete is prepared from the cement modified asphalt, natural aggregate and phosphogypsum filler.
[0026] 1) The waste phosphogypsum is washed, dried, ground and screened to obtain phosphogypsum powder;
[0027] The asphalt is heated to a molten state at 150-160 °C, and then 2.5% of cement powder relative to the mass of the asphalt is added, and stirred at a low speed for 30 min to prepare the cement modified asphalt;
[0028] According to the aggregate gradation of the water-resistant / freeze-resistant phosphogypsum asphalt concrete and the oil-stone ratio of 5.2%, the cement modified asphalt, natural aggregate and phosphogypsum powder obtained in step 1) (instead of mineral powder) are quantitatively weighed;
[0029] 4) According to the designed mixing ratio, the heated and molten cement modified asphalt, aggregate and phosphogypsum filler dried at 160-170 °C for at least 4 h are mixed at 150-160 °C to prepare the water-resistant / freeze-resistant phosphogypsum asphalt concrete.
[0030] Performance test: According to the Highway Engineering Asphalt and Asphalt Mixture Test Regulation (JTG E20-2011), the performance of 2.5% cement modified asphalt mixture was tested. The Marshall stability of the water-resistant / freeze-resistant phosphogypsum asphalt concrete was 13.20 kN, the Marshall stability improvement rate was 88.3%, the splitting tensile strength was 1.18 MPa, the splitting strength improvement rate was 81.5%, and at the same time, the immersion Marshall residual stability was 92.2%, and the freeze-thaw splitting residual strength ratio was 90.4%, which was much higher than the 85% immersion Marshall residual stability and 80% freeze-thaw splitting residual strength ratio required by the Highway Asphalt Pavement Construction Technical Specification (JTG F40-2004). It can be seen that the water-resistant / freeze-resistant phosphogypsum asphalt concrete mixed with 2.5% cement not only improves the Marshall stability and splitting tensile strength, but also has better water damage resistance and resistance to damage. This is because cement, as an alkaline substance, will react with acidic substances in asphalt to enhance the adhesion between asphalt and aggregate, and cement can also hydrate on the surface of aggregate and phosphogypsum in a humid environment, strengthening the interfacial bonding strength between asphalt and aggregate, phosphogypsum, and improving the water and frost resistance of phosphogypsum asphalt concrete.
[0031] Example 2
[0032] In this embodiment, the cement content is selected as 5%, and the other steps remain the same as in Example 1.
[0033] Performance test: According to the Highway Engineering Asphalt and Asphalt Mixture Test Regulation (JTG E20-2011), the performance of 5% cement composite modified asphalt and its mixture was tested. The Marshall stability of the water-resistant / freeze-resistant phosphogypsum asphalt concrete was 14.68 kN, the Marshall stability improvement rate was 109.4%, the splitting tensile strength was 1.29 MPa, the splitting strength improvement rate was 98.5%, and at the same time, the immersion Marshall residual stability was 92.3%, and the freeze-thaw splitting residual strength ratio was 91.2%, which was much higher than the 85% immersion Marshall residual stability and 80% freeze-thaw splitting residual strength ratio required by the Highway Asphalt Pavement Construction Technical Specification (JTG F40-2004). It can be seen that compared with Example 1, 5% cement does not continue to significantly improve the water damage resistance of water-resistant / freeze-resistant phosphogypsum asphalt concrete, but the Marshall stability and splitting tensile strength are further improved, indicating that the resistance to damage is still increasing. This may be because as the cement content increases, the cement reacts more fully with the acidic substances in the asphalt, the interfacial bonding of asphalt to aggregate and phosphogypsum continues to strengthen, resulting in further improvement in the mechanical properties and water stability of the prepared phosphogypsum asphalt mixture.
[0034] Example 3
[0035] The cement content in this embodiment is selected as 7.5%, and other steps are consistent with those in embodiment 1.
[0036] Performance test: the performance of the 7.5% cement composite modified asphalt mixture is tested according to the "Highway Engineering Asphalt and Asphalt Mixture Test Regulation" (JTG E20-2011). The Marshall stability of the water-resistant / freeze-resistant phosphogypsum asphalt concrete is 14.68 kN, the Marshall stability improvement rate is 92.2%, the splitting tensile strength is 1.26 MPa, the splitting strength improvement rate is 93.8%, the immersed Marshall residual stability is 92.8%, and the freeze-thaw splitting strength ratio is 91.5%, which is much higher than the 85% immersed Marshall residual stability and 80% freeze-thaw splitting residual strength ratio required by the "Highway Asphalt Pavement Construction Technical Specification" (JTG F40-2004). It can be seen that compared with embodiment 2, with the continuous increase of the cement content, the 7.5% cement does not continue to improve the water damage resistance of the water-resistant / freeze-resistant phosphogypsum asphalt concrete, and due to the incorporation of too much cement, it leads to uneven distribution in the asphalt and adsorption of the structure asphalt and free asphalt inside and outside the structure film on the surface of the mineral aggregate, resulting in a decrease in the adhesion between the asphalt and the natural aggregate and the phosphogypsum, a slight decrease in the Marshall stability, and a decrease in the ability to resist force damage. According to the test results of embodiments 1, 2 and 3, when the cement content exceeds 5%, the Marshall stability improvement rate and the splitting strength improvement rate of the phosphogypsum asphalt concrete will decrease, but the immersed Marshall stability and the freeze-thaw splitting residual strength ratio have no further improvement. Therefore, considering the engineering performance and economic benefit factors, the optimal cement content is determined to be 5%.
[0037] Embodiment 4
[0038] The water-resistant / freeze-resistant phosphogypsum asphalt concrete is prepared from PU / cement composite modified asphalt, natural aggregate and phosphogypsum powder.
[0039] 1) The recycled waste phosphogypsum is treated by washing with water, drying and grinding to obtain phosphogypsum powder;
[0040] The asphalt is heated to a molten state at 150-160°C, then 2% PU and 5% cement powder are added relative to the mass of the asphalt, and low-speed stirring is performed for 30 min to prepare PU / cement modified asphalt;
[0041] According to the aggregate gradation of the water-resistant / freeze-resistant phosphogypsum asphalt concrete and the 5.2% oil aggregate ratio, the PU / cement composite modified asphalt, natural aggregate and phosphogypsum powder (instead of mineral powder) obtained in step 1) are quantitatively weighed;
[0042] 4) According to the designed mixing ratio, the heated and molten flowing PU / cement composite modified asphalt is mixed with the aggregate and phosphogypsum filler dried at 160-170℃ for at least 4h at 150-160℃ to prepare the water / freeze resistant phosphogypsum asphalt concrete.
[0043] Performance test: According to the Highway Engineering Asphalt and Asphalt Mixture Test Regulation (JTG E20-2011), the performance test is conducted on the 2% PU / 5% cement composite modified asphalt mixture, the Marshall stability of the water / freeze resistant phosphogypsum asphalt concrete is 14.21 kN, the Marshall stability improvement rate is 102.7%, the splitting tensile strength is 1.03 MPa, the splitting strength improvement rate is 58.5%, the simultaneous immersion Marshall residual stability is 92.4%, and the freeze-thaw splitting strength ratio is 92.8%, which is still much higher than the 85% immersion Marshall residual stability and 80% freeze-thaw splitting residual strength ratio required by the Highway Asphalt Pavement Construction Technical Specification (JTG F40-2004). It can be seen that, compared with Example 2, this embodiment adds 2% PU on the basis of 5% cement, and the significant mechanical property change is that the splitting tensile strength of the asphalt concrete decreases significantly, and the freeze-thaw splitting strength ratio increases, which is due to the fact that a small amount of PU only causes local organic cementation in the interface region of the phosphogypsum asphalt concrete under the cementation of cement, resulting in some weak parts in the interface transition region and easy stress failure.
[0044] Example 5
[0045] In this embodiment, the PU content is selected as 4%, and the other steps are consistent with Example 4.
[0046] Performance test: The physical performance of the 4% PU / 5% cement composite modified asphalt mixture was tested according to the Highway Engineering Asphalt and Asphalt Mixture Test Regulation (JTG E20-2011). The Marshall stability of the water / anti-freeze type phosphogypsum asphalt concrete was 15.98 kN, the Marshall stability improvement rate was 127.9%, the splitting tensile strength was 1.41 MPa, the splitting strength improvement rate was 116.9%, the water-soaked Marshall residual stability was 92.6%, and the freeze-thaw splitting strength ratio was 94.6%, which were much higher than the 85% water-soaked Marshall residual stability and 80% freeze-thaw splitting residual strength ratio required by the Highway Asphalt Pavement Construction Technical Specification (JTG F40-2004). It can be seen that, compared with Example 4, with the increase of the PU content, the Marshall stability and splitting tensile strength of the water / anti-freeze type asphalt mixture are significantly improved, and the water-soaked Marshall stability and freeze-thaw splitting strength ratio are still improved. This result shows that with the increase of the PU content, the organic-inorganic cementitious structure system formed is more stable, and the adhesion of asphalt to natural aggregate and phosphogypsum is stronger, thereby further improving the mechanical strength and water and freeze resistance of the phosphogypsum asphalt concrete.
[0047] Example 6
[0048] In this example, the PU content was selected as 6%, and the other steps were consistent with Example 4.
[0049] Performance test: The physical performance of the 4% PU / 5% cement composite modified asphalt mixture was tested according to the Highway Engineering Asphalt and Asphalt Mixture Test Regulation (JTG E20-2011). The Marshall stability of the water / anti-freeze type phosphogypsum asphalt concrete was 15.98 kN, the Marshall stability improvement rate was 127.9%, the splitting tensile strength was 1.41 MPa, the splitting strength improvement rate was 116.9%, the water-soaked Marshall residual stability was 92.6%, and the freeze-thaw splitting strength ratio was 94.6%, which were much higher than the 85% water-soaked Marshall residual stability and 80% freeze-thaw splitting residual strength ratio required by the Highway Asphalt Pavement Construction Technical Specification (JTG F40-2004). It can be seen that, compared with Example 4, with the increase of the PU content, the Marshall stability and splitting tensile strength of the water / anti-freeze type asphalt mixture are significantly improved, and the water-soaked Marshall stability and freeze-thaw splitting strength ratio are still improved. This result shows that with the increase of the PU content, the organic-inorganic cementitious structure system formed is more stable, and the adhesion of asphalt to natural aggregate and phosphogypsum is stronger, thereby further improving the mechanical strength and water and freeze resistance of the phosphogypsum asphalt concrete.
[0050] Comparative Example 1
[0051] In this comparative example, the mineral powder used was phosphogypsum powder that was not washed with water or calcined.
[0052] 1) The untreated waste phosphogypsum was ground and sieved to obtain phosphogypsum powder with a particle size of 0.075 mm or less, which was not washed with water or calcined;
[0053] According to the aggregate gradation of water-resistant / freeze-resistant type and the oil-stone ratio of 5.2%, 70# base asphalt, natural aggregate and the phosphogypsum powder obtained in step 1) (instead of mineral powder) are quantitatively weighed;
[0054] 4) According to the designed mixing ratio, the 70# base asphalt heated and melted in flow is mixed with the aggregate and phosphogypsum filler dried at 160-170℃ for at least 4h at 150-160℃ to prepare asphalt concrete.
[0055] Performance test: the performance of the mixture is tested according to the "Highway Engineering Asphalt and Asphalt Mixture Test Regulation" (JTG E20-2011), the Marshall stability of the phosphogypsum asphalt concrete is 7.01kN, the splitting tensile strength is 0.65MPa, the residual Marshall stability after immersion is 70.9%, which is lower than the requirement of 80% in the "Highway Asphalt Pavement Construction Technical Specification" (JTG F40-2004), and the freeze-thaw splitting strength ratio is 76.3%, which is slightly higher than the requirement of 75% in the specification. It can be seen that the mechanical properties and water resistance and frost resistance of the phosphogypsum asphalt concrete prepared directly by using unmodified base asphalt are at a low level, and the overall cannot meet the road technical standard.
[0056] Comparative Example 2:
[0057] In the present comparative example, the mineral powder used is phosphogypsum powder treated by water washing, calcination, grinding and sieving, and the other steps are the same as those in Comparative Example 1.
[0058] Performance test: the performance of the mixture is tested according to the "Highway Engineering Asphalt and Asphalt Mixture Test Regulation" (JTG E20-2011), the Marshall stability of the phosphogypsum asphalt concrete is 7.69kN, the Marshall stability improvement rate is 9.7%, the splitting tensile strength is 0.79MPa, the splitting strength improvement rate is 21.5%, the residual Marshall stability after immersion is 74.8%, which is lower than the requirement of 80% in the "Highway Asphalt Pavement Construction Technical Specification" (JTG F40-2004), and the freeze-thaw splitting strength ratio is 83.9%, which is slightly higher than the requirement of 75% in the specification. Compared with Comparative Example 1, all the relevant technical indicators are improved to a certain extent, but the Marshall stability, splitting tensile strength and residual Marshall stability after immersion of the phosphogypsum asphalt concrete are still at a low level, and still overall cannot meet the road technical standard.
[0059] To further illustrate the above problems, the test phenomena are shown in Table 1.
[0060] Table 1
[0061]
[0062]
[0063] To further illustrate the above problem, the Marshall stability test and immersion Marshall test results are shown in Table 2.
[0064] Table 2
[0065]
[0066] Note: *Marshall stability improvement rate is the percentage of the Marshall stability ratio of Examples 1-6 and Comparative Example 2 to Comparative Example 1.
[0067] **The freeze-thaw splitting strength of Examples 1-6 is greater than or equal to 80% of the standard, and the freeze-thaw splitting strength of Comparative Examples 1 and 2 is greater than or equal to 75% of the standard.
[0068] To further illustrate the above problem, the freeze-thaw splitting test and splitting tensile test results are shown in Table 3.
[0069] Table 3
[0070]
[0071] Note: *Splitting strength improvement rate is the percentage of the splitting strength ratio of Examples 1-6 and Comparative Example 2 to Comparative Example 1.
[0072] **The freeze-thaw splitting strength of Examples 1-6 is greater than or equal to 80% of the standard, and the freeze-thaw splitting strength of Comparative Examples 1 and 2 is greater than or equal to 75% of the standard.
[0073] From the test results of Comparative Examples 1-2, the immersion Marshall residual stability of asphalt concrete without cement is 70.9% and 74.8%, respectively, which is lower than the standard requirement of 80%, and does not meet the relevant requirements of the "Highway Asphalt Pavement Construction Technical Specification" (JTG F40-2004) for water damage resistance of asphalt concrete. Moreover, there are obvious particle loss and peeling phenomena during the test, which directly proves that the water damage resistance of the phosphogypsum asphalt concrete is poor.
[0074] Compared with Comparative Example 2, the test results of Examples 1, 2 and 3 show that the incorporation of 2.5%, 5% and 7.5% cement can significantly improve the Marshall stability, the tensile strength in the splitting test, the residual Marshall stability after immersion and the splitting strength ratio after freeze-thaw of the phosphogypsum asphalt concrete, indicating that the cement plays a positive role in improving the mechanical strength and water stability of the water-resistant / freeze-resistant phosphogypsum asphalt concrete. In addition, as can be seen from Comparative Examples 2 and 3, the increase of the cement content has no further obvious improvement effect on the residual Marshall stability after immersion and the splitting strength ratio after freeze-thaw of the water-resistant / freeze-resistant phosphogypsum asphalt concrete. At the same time, when the cement content is 5%, the Marshall stability of the water-resistant / freeze-resistant phosphogypsum asphalt concrete has the highest improvement rate. Therefore, the use of only 5% cement can achieve a significant improvement effect on the water damage resistance of the water-resistant / freeze-resistant phosphogypsum asphalt concrete.
[0075] Compared with Example 2, the test results of Examples 4, 5 and 6 show that the incorporation of 2%, 4% and 6% PU and 5% cement can significantly improve the Marshall stability of the phosphogypsum asphalt concrete, and the residual Marshall stability after immersion and the splitting strength ratio after freeze-thaw are also improved, indicating that the organic-inorganic cementitious system formed by the joint action of PU and cement has the ability to further improve the water damage resistance of the water-resistant / freeze-resistant phosphogypsum asphalt concrete. In addition, as can be seen from Comparative Examples 5 and 6, the increase of the PU content has no further obvious improvement effect on the residual Marshall stability after immersion and the splitting strength ratio after freeze-thaw of the water-resistant / freeze-resistant phosphogypsum asphalt concrete. Compared with Example 2, the tensile strength in the splitting test of Example 4 has a certain degree of decrease, which may be that a small amount of PU can only cause local organic cementation in the interface region of the phosphogypsum asphalt concrete under the cementation of cement, resulting in some weak parts in the interface transition region and easy stress failure. When the PU content is 4% and the cement content is 5% (Example 5), the Marshall stability of the water-resistant / freeze-resistant phosphogypsum asphalt concrete has an improvement rate of 127.9%, the tensile strength in the splitting test has an improvement rate of 116.9%, the residual Marshall stability after immersion is 92.6%, and the splitting strength ratio after freeze-thaw is 94.6%. However, when the PU content is further increased to 6% and the cement content remains 5% (Example 6), there is no obvious change in the relevant data. Therefore, the technical solution of Example 5 has a significant effect of comprehensively improving the water and freeze damage resistance of the phosphogypsum asphalt concrete, and can also enhance the resistance to stress failure, showing significant economic benefits and engineering value.
[0076] The above only describes the preferred embodiment of the present application, the organic material and inorganic material modifier used in the organic-inorganic cementitious system of the present application includes but is not limited to PU and cement, and the gradation used includes but is not limited to the synthetic gradation used in Examples 1-6 and Comparative Examples 1-2. It should be noted that for those skilled in the art, several improvements and refinements can be made without departing from the principles of the present application, and these improvements and refinements should also be considered as falling within the scope of the present application.
[0077] The basic principles and main features of the present application and the advantages of the present application are shown and described above, and it is obvious for those skilled in the art that the present application is not limited to the details of the above exemplary embodiments, and the present application can be implemented in other specific forms without departing from the spirit or essential characteristics of the present application. Therefore, the embodiments should be considered as exemplary and non-limiting from any point of view, and the scope of the present application is defined by the appended claims rather than the above description, and therefore all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be encompassed by the present application. Any reference signs in the claims should not be considered as limiting the claims involved.
[0078] Furthermore, it should be understood that although the present specification is described in terms of embodiments, not every embodiment contains only one independent technical solution, and the description of the specification is only for the sake of clarity, and those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that those skilled in the art can understand.
Claims
1. A water-resistant, freeze-thaw resistant, cementitious stabilized phosphogypsum asphalt concrete, characterized in that: The raw materials for this asphalt concrete include polyurethane / cement composite modified asphalt, natural aggregate, and phosphogypsum. The phosphogypsum filler is fine powder obtained by washing, calcining, and grinding waste phosphogypsum. The asphalt is heated to a molten state at 150-160℃, and then 4% of polyurethane prepolymer and 5% of cement powder relative to the asphalt mass are added. The mixture is stirred at low speed for 30 minutes to prepare the polyurethane / cement composite modified asphalt. The natural aggregate is a continuously graded aggregate made from crushed limestone. Based on the aggregate gradation of the water-resistant phosphogypsum asphalt concrete and an asphalt-aggregate ratio of 5.2%, the polyurethane / cement composite modified asphalt, the natural aggregate, and the phosphogypsum are weighed quantitatively.
2. A method for preparing water-freezing resistant, cementitious stabilized phosphogypsum asphalt concrete, characterized in that, This preparation method is used to prepare the asphalt concrete as described in claim 1, and mainly includes the following steps: Step 1: The recycled waste phosphogypsum is washed, dried and ground to obtain phosphogypsum powder. Step 2: After heating the asphalt to a molten state at 150~160℃, add 4% polyurethane prepolymer and 5% cement powder relative to the asphalt mass, stir at low speed for 30 minutes to prepare the polyurethane / cement composite modified asphalt. Step 3: Based on the aggregate gradation of the water-resistant phosphogypsum asphalt concrete and the asphalt-aggregate ratio of 5.2%, weigh out the polyurethane / cement composite modified asphalt, natural aggregate, and the phosphogypsum powder obtained in Step 1 in a quantitative manner; the natural aggregate is a continuously graded aggregate made from crushed limestone. Step 4: According to the designed mix proportion, the polyurethane / cement composite modified asphalt, aggregate and phosphogypsum filler are mixed to prepare water-resistant phosphogypsum asphalt concrete with organic / inorganic composite stabilized phosphogypsum.
3. The method for preparing a water-freezing resistant, cementitious stabilized phosphogypsum asphalt concrete according to claim 2, characterized in that: The particle size of the phosphogypsum filler is 0~0.075mm; the asphalt is 70# base asphalt.
4. The method for preparing a water-freezing resistant, cementitious stabilized phosphogypsum asphalt concrete according to claim 2, characterized in that: The natural aggregate has a particle size of 0.075~16mm.
Citation Information
Cited By
Activated phosphogypsum-polyurethane composite modified asphalt and ultrasonic synergistic preparation method thereof
CN121991520A